2019
DOI: 10.1111/ssqu.12750
|View full text |Cite
|
Sign up to set email alerts
|

A Cultural Theory of Partisanship and Policy Attitudes

Abstract: Objective Political parties provide an important function for a public that is generally seen as not consistently ideological by guiding its thinking about policy issues. In this article, we examine whether the four cultural worldviews derived from grid‐group cultural theory—hierarch, egalitarian, individualist, and fatalist—are predictive of partisan attachments and perceptions of climate change risk among the public. Methods Data come from an original survey of the U.S. public conducted in 2011 and 2012. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…For social scientists studying public opinion and such topics as political culture, the culture wars, ideology, value structure, mass belief systems, partisanship, political sophistication, political participation, policy preferences, risk perceptions, and many other subjects, CT provides rich theoretical resources. Its operationalization in survey research provides fresh insights and often greater explanatory and predictive power than alternative theories and concepts, including left–right ideology and partisanship (see, e.g., Ellis and Thompson, 1997; Gastil et al., 2011; Grendstad, 2000, 2001, 2003a, 2003b; Grendstad and Selle, 1997, 1999; Herron and Jenkins‐Smith, 2006; Jackson, 2014; Johnson and Swedlow, 2019b; Johnson, Swedlow, and Mayorga, 2019; Jones, 2011; Kahan et al., 2010a, 2010b; Kiss, Lachapelle, and Montpetit, 2020; Lachapelle, Montpetit, and Gauvin, 2014; Maleki and Hendriks, 2015; Nowlin and Rabovsky, 2019; Olli, 2012; Ripberger, Jenkins‐Smith, and Herron, 2011; Ripberger et al., 2012, 2014; Swedlow et al., 2016a; Trousset et al., 2015; Wildavksy and Dake, 1990; Xue et al, 2014). However, with the exception of predictive validity (focusing mostly on effect sizes) (Kahan, 2012; Marris et al., 1998; Rippl, 2002; Sjoeberg, 1998, 2003, 2005a, 2005b), the construct validity of the survey measures used in these studies has not begun to be assessed until recently (Cambardella et al., 2020; Johnson and Swedlow, 2019a, 2019b; Johnson, Swedlow, and Mayorga, 2019; Swedlow et al., 2016b; Xue et al., 2014, 2016).…”
Section: What Is Cultural Theory? and How Has It Been Operationalizedmentioning
confidence: 99%
See 1 more Smart Citation
“…For social scientists studying public opinion and such topics as political culture, the culture wars, ideology, value structure, mass belief systems, partisanship, political sophistication, political participation, policy preferences, risk perceptions, and many other subjects, CT provides rich theoretical resources. Its operationalization in survey research provides fresh insights and often greater explanatory and predictive power than alternative theories and concepts, including left–right ideology and partisanship (see, e.g., Ellis and Thompson, 1997; Gastil et al., 2011; Grendstad, 2000, 2001, 2003a, 2003b; Grendstad and Selle, 1997, 1999; Herron and Jenkins‐Smith, 2006; Jackson, 2014; Johnson and Swedlow, 2019b; Johnson, Swedlow, and Mayorga, 2019; Jones, 2011; Kahan et al., 2010a, 2010b; Kiss, Lachapelle, and Montpetit, 2020; Lachapelle, Montpetit, and Gauvin, 2014; Maleki and Hendriks, 2015; Nowlin and Rabovsky, 2019; Olli, 2012; Ripberger, Jenkins‐Smith, and Herron, 2011; Ripberger et al., 2012, 2014; Swedlow et al., 2016a; Trousset et al., 2015; Wildavksy and Dake, 1990; Xue et al, 2014). However, with the exception of predictive validity (focusing mostly on effect sizes) (Kahan, 2012; Marris et al., 1998; Rippl, 2002; Sjoeberg, 1998, 2003, 2005a, 2005b), the construct validity of the survey measures used in these studies has not begun to be assessed until recently (Cambardella et al., 2020; Johnson and Swedlow, 2019a, 2019b; Johnson, Swedlow, and Mayorga, 2019; Swedlow et al., 2016b; Xue et al., 2014, 2016).…”
Section: What Is Cultural Theory? and How Has It Been Operationalizedmentioning
confidence: 99%
“…and Mayorga, 2019;Jones, 2011;Kahan et al, 2010aKahan et al, , 2010bKiss, Lachapelle, and Montpetit, 2020;Lachapelle, Montpetit, and Gauvin, 2014;Maleki and Hendriks, 2015;Nowlin and Rabovsky, 2019;Olli, 2012;Ripberger, Jenkins-Smith, and Herron, 2011;Ripberger et al, 2012Ripberger et al, , 2014Swedlow et al, 2016a;Trousset et al, 2015;Wildavksy and Dake, 1990;Xue et al, 2014). However, with the exception of predictive validity (focusing mostly on effect sizes) (Kahan, 2012;Marris et al, 1998;Rippl, 2002;Sjoeberg, 1998Sjoeberg, , 2003Sjoeberg, , 2005aSjoeberg, , 2005b, the construct validity of the survey measures used in these studies has not begun to be assessed until recently (Cambardella et al, 2020;Swedlow, 2019a, 2019b;Johnson, Swedlow, and Mayorga, 2019;Swedlow et al, 2016b;Xue et al, 2014Xue et al, , 2016.…”
mentioning
confidence: 99%
“…Policy core beliefs are applicable to a subsystem and are informed by deep core beliefs. For example, an egalitarian worldview as a deep core belief informs the policy core belief that climate change poses significant risks (Jones, 2011; Nowlin & Rabovsky, 2020). Finally, secondary beliefs are constrained by both deep core and policy core beliefs and are focused on a set of narrow concerns within a policy domain (e.g., levels of budget authority).…”
Section: A Logic Of Policy Learningmentioning
confidence: 99%
“…Hierarchs prefer social arraignments with clear lines of authority within clearly defined groups, and their views on climate change tend to be muddled and associated with their political beliefs. Specifically, Nowlin and Rabovsky (2020) found that, on average, increasing hierarchical beliefs was not associated with perceived risk from climate change; however, liberal hierarchs perceived increasing risk from climate change, whereas conservative hierarchs perceived less risk from climate change. Additionally, work using cultural cognition theory pairs hierarchy with individualism and finds that hierarch‐individualists tend not to perceive climate change as a risk (Kahan et al, 2012; Nowlin, 2019).…”
Section: Climate Change Polarization and Public Opinionmentioning
confidence: 99%
“…Cultural theory is based on ideal social relationships within societies, which makes it a useful framework for examining which actors and institutions the public thinks should be doing more to address the climate crisis. Additionally, views on climate change are highly polarized across cultural types, particularly between egalitarians and individualists (Jones, 2011; Kahan et al, 2012; Nowlin & Rabovsky, 2020).…”
Section: Introductionmentioning
confidence: 99%